Tourism e-marketing applied to the dissemination of real estate heritage property of Portoviejo city - Celorio Manzaba, Jonathan Steven (2024)
Heritage tourism should be integrated into tourism planning to preserve the culture of communities and contribute to local development. This research aimed to develop an e-marketing plan for promoting the real estate assets of Portoviejo, located in the Manabí province of Ecuador. The research methodology employed was a mix of non-experimental and exploratory approaches. By applying analytical techniques and collecting data, we identified and characterised 23 real estate assets in Portoviejo with great potential for cultural tourism. We used local methodologies from Instituto Nacional de Patrimonio Cultural del Ecuador (INPC) and Ministerio de Turismo del Ecuador. Also, we conducted interviews with local actors involved in the management and maintenance of cultural heritage. Finally, we developed strategies to utilise digital platforms to promote cultural tourism in the area and contribute to local tourism development through these real estate assets.